ANALISIS RIGIDITAS LENDING RATE PERBANKAN DI INDONESIA PERIODE JANUARI2001 - JUNI2004 - Sutomo, Sutomo; Johadi, Johadi (Universitas Muhammdaiyah Surakarta, 2004)
The research aims to know the influence of interest rate ofSBI, exchange rate, total bank lending, supply of funds and commercial bank amount to rigidly bank lending rate in Indonesian period of January 2001 until June 2004. The research use secondary data by character of time series. The research methodology used a partial adjustment model that rigidly bank lending rate are influence by all independent variable such interest rate of SBI, exchange rate, and total bank lending, supply of fund and commercial bank amount in banking sector. The empirical results that rigidly bank lending rate are influenced by all independent variable are collectively such interest rate of SBI, exchange rate, and total bank lending, supply of fund and commercial bank amount in banking sector. But as partial, rigidly bank-lending rate are influenced by an interest rate of SBI, exchange rate, total bank lending and supply of funds and commercial bank amount, which dont have an effect to rigidly bank lending rate.The result that is suitable with the theory, where monetary instrument (interest rate of SBI) can be used to influence bank-lending rate as process transmission mechanism monÂetary policy by price channel approach. Adjustment coefficient is equal to 0,5484 which meaning 54,84 % represents the difference between bank lending rate actual with bank lending rate that desired which fulfilled to be reached in one period, where speed of adjustment bank lending rate in response change of independent variable equal to 5 months 27 day, with mean lag independent variable equal to 1,1812867 months.